The Passive Origin of the Institutionalization of Power Inequality in the Meaning/Experience of Womanhood in Igboland - Ekweariri, Dominic (Frontiers in Sociology, 2020)
Abstract: This study, which analyzes the meaning and experience of womanhood in Igbo land, reveals a power inequality, captured by the depiction of women as the property of men. Though most of the intuitions found in poststructuralism might be confirmed in our analysis (e.g. that discourse produces the subjects and that language operates alongside power and social control), my greatest motivation in this essay is different: it proposes that power inequality as evident in the depictions of women and their oppressive subordinating consequences therein are not consciously intended by all classes of agents while acting in accordance with normal rules and accepted practice; an aspect that is usually lacking in other accounts of the institutionalisation of social realities where dominant discourse, collective intentionality etc., are usually emphasised. Whence the questions: What is then the origin of unequal power distribution among the sexes? And what is the origin of unintended but oppressive images and subordinating depictions of women as the property and unequal of men? Inspired by Sartre, I make an elaborate use of passive synthesis as developed by Husserl’s analysis of perceptual objects and phenomenological perception of time consciousness, and as found in Merleau Ponty’s habituation to respond to these questions.